ENVIRONMENTALLY SUSTAINABLE TECHNOLOGIES AND ENVIRONMENTAL QUALITY INDICATORS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Despite the fact that environmental indicators are investigated for long time the solving o f indicators problems is far of completion yet. Paper discusses the results of investigation environmental indicators in conformity with quality of environmentally sound technologies and their impact on man's life quality. As a result o f investigations three groups of indicators were worked up: 1) for environment quality in cities - anthropogenic pressure indicators on atmosphere, water and earth, 2) for estimation of technologies, containing information about useful exploited natural resources and utilization waste products, 3) for assessment mutual changes of environment quality and man’s living quality. The paper offers equations which characterize possibilities for development o f industry on the principles of sustainable development.